Damage detection in large composite stiffened panels based on a novel SHM building block philosophy. (22nd February 2021) - Yue, Nan; Khodaei, Zahra Sharif; Aliabadi, M H
Abstract: This paper proposes a structural health monitoring (SHM) building block (BB) approach for guided wave based structural health monitoring (GWSHM) of large composite stiffened panel subjected to varying temperature conditions. The proposed approach follows a similar philosophy to industrial substantiation of composite structures through BB by conducting SHM analysis and associated tests at different levels of structural complexity, beginning with small coupon specimens and progressing through structural elements and details (mono-stringer) and finally sub-components (large stiffened composited panel). Each level builds on the knowledge gained at previous, less complex levels. The detection of multiple barely visible impact damage (BVID) in the large panels is achieved by outlier analysis using a reference pristine database gathered from simple coupons and mono-stringer panels under a wide range of temperature variation. This approach enables the data utilisation from lower-level structure in the proposed BB test scheme to higher-level structures and hence reduce the number of tests required for large and complex structures. The detected damage is then localised by a proposed two-step multi-damage localisation method, which first confirms the presence of the damage and narrows down the damaged section then provides an enhanced damage imaging for precise location estimation. Damage detection with a true positive rate of 0.909 and a false positive rate of 0.111 as well as accurate multiple damage localisation are achieved in the flat fuselage panels for a temperature range of 25 °C–50 °C.